PENGARUH SUHU PENYIMPANAN TERHADAP KECEPATAN RESPIRASI: MODEL RESPIRASI PISANG "CAVENDISH" - Utomo, Adrianus Rulianto (Jurnal Teknologi Pangan dan Gizi, 2003)
A respiration model, based on enzyme kinetic, was proposed for predicting respiration rates of Cavendish Banana as a function of O2 and CO2. Respiration rate were measured with the close system. Cavendish Bananas were kept in close glass jars, covered with rigid cover. Sampling of head space gas was done every 2x24 hr for 3 weeks and the gas were analyzed for O2 and CO2 by gas chromatography. The experiments were conducted at 10°C (refrigeration), 20°C (air conditioner room) and 30°C (room temperature). It was found that maximum respiration rate was affected by storage temperature. Using the Arrbenius plot, it showed that the higher storage temperature the faster respiration rate.